CURRENT TRENDS OF LOCAL SELF-GOVERNMENT IN THE RUSSIAN FEDERATION - B. V. Karzev; N. N. Musinova (Вестник университета, 2020)
Current trends in the development of local self-government in the Russian Federation, born of global challenges to social development have been considered. Positive trends have been identified and problem areas in the development of local self-government that emerged as a result of state legal regulation of local self-government powers, such as: their content, differentiation, transfer, and redistribution, have been defined. The causes of existing problems have been diagnosed. The necessity of optimization of the system of municipal powers has been substantiated and it is proposed, primarily on the level of Federal legislation, to give legal status issues of joint competence of the Russian Federation subjects and local self-government and to determine the principles of bodies of state authority of the Russian Federation of powers in subjects of joint conducting subjects of the Russian Federation and bodies of local self-government.